A survey on stationary problems, Green's functions and spectrum of Sturm–Liouville problem with nonlocal boundary conditions - Štikonas, Artūras (Nonlinear Analysis: Modelling and Control, 2014)
In this paper, we present a survey of recent results on the Green's functions and on spectrum for stationary problems with nonlocal boundary conditions. Results of Lithuanian mathematicians in the field of differential and numerical problems with nonlocal boundary conditions are described.*The research was partially supported by the Research Council of Lithuania (grant No. MIP-047/2014).